FAKTOR – FAKTOR INTERNAL YANG BERPENGARUH TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia) - Prama Handitya Wardhana; Darsono Darsono (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to analyze the factors that affect audit report lag of financial reports to the manufacturing companies listed on the Indonesia Stock Exchange. The examined factors of this research are solvability, liquidity, ownership concentration, board independence and audit committee as the independent variable, profitability and size company as the control variable, while the audit report lag as the dependent variable. The sample consists of 440 companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to Bapepam in the period 2010-2012. The data that was used in this research was secondary data and selected by using purposive sampling method. Model analysis using multiple linear regression analysis. Using the F-test to determine the effect of simultaneous between company characteristics and capital structure. Using t-test to examine the partial correlation of each independent variable on capital structure. Based on analytical results shows that only variable ownership concentration have significant influence toward audit report lag, while variable solvability, liquidity, board independence and audit committee doesn’t have significant influence toward audit report lag.